Strategic Spiritual Leadership in Strengthening Religious Character through Religious Values (A Multisite Study at TK Plus Al Abrar and TK Wahid Hasyim, Bangil District) - Nawirah Nawirah; Taufiq Haris; M furqon Wahyud (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Early childhood education plays a crucial role in shaping children's religious character. Strengthening religious character requires leadership strategies capable of integrating spiritual values into the school culture. This study aims to describe the strategic management of spiritual leadership in strengthening religious character based on religious values at TK Plus Al Abrar and TK Wahid Hasyim in Bangil District, identify the factors influencing its implementation, and analyze its implications. The study employed a qualitative approach using a multisite research design. Data were collected through in-depth interviews, observations, and document analysis. The findings revealed that the principals’ spiritual leadership was manifested through the planning of religious programs, the organization of school resources, the implementation of religious habituation activities, and continuous evaluation. The primary supporting factors included principals’ commitment, teachers’ role modeling, a religious school culture, and parental support. The implementation of spiritual leadership strategies contributed to improved discipline in religious practices, the development of positive social behaviors, and the sustainable formation of students’ religious character. These findings highlight the importance of strategic spiritual leadership in fostering value-based character education within early childhood education settings.